Productivity and the Density of Economic Activity - Ciccone, Antonio; Hall, Robert E. (American Economic Review, 1996)
To explain the large differences in labor productivity across U.S. states we estimate two models–one based on local geographical externalities and the other on the diversity of local intermediate services–where spatial density results in aggregate increasing returns. Both models lead to a relation between county employment density and productivity at the state level. Using data on gross state output we find that a doubling of employment density increases average labor productivity by around 6 percent. More than half of the variance of output per worker across states can be explained by differences in the density of economic activity.